Reporte De Caso Clínico Sobre Paciente Canino Macho Con Brucelosis Canina E Informe De Pasantía (2023)
The veterinary clinic of the Antonio Nariño University provides comprehensive outpatient and specialist veterinary medical services in the areas of Cardiology, Orthopedics, Dentistry, Surgery, Imaging, and care for unconventional pets for the university community and the neighboring community of the sector.